SOCIALIZATION OF SIMPLE CAR MAINTENANCE IN INTAN ISLAND, TANJUNG HARAPAN VILLAGE, PANGKATAN VILLAGE - Sipahutar, Prayogi Darmansyah; Prayoga, Yudi; Halim, Abd (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This socialization raised the theme of the importance of maintaining simple cars for the community. This issue was raised because many people are currently driving private cars but they don't know how to maintain a car. This socialization was made into a public service advertisement that informs public drivers how to maintain cars in a good way. The main purpose of this socialization is for drivers to get information about car maintenance and be able to apply it daily.